Penguatan Nilai Akidah Dan Listening Skill Bagi Siswa Sekolah Sahabat Alam Melalui Konten Religi Berbahasa Inggris - Zaitun Qomariah; Hesty Widiastuty; Iffa Kharimah; Winna Winna; Lafifah Suliyya (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2024)
This research aims to explore innovative approaches in integrating English-language religious content as a means of strengthening religious values ​​and improving listening skills in junior high school students at Alam School. This research uses a descriptive method, an innovative approach that illustrates the condition of the subject or object of research by detailing existing facts. The results of the research show that community service activities that use English religious content are successful in strengthening religious values ​​and improving students' listening skills. Students are able to understand and remember new vocabulary through listening to videos. They can also internalize the moral values ​​contained in the video. Apart from that, the use of gamification through the Kahoot application can motivate students to learn in an interactive and fun way. An innovative learning approach that integrates elements of religion and English can help students develop holistically, both spiritually, morally and in language skills. This approach can be an alternative that can be applied in learning English at school.